Functional consequences of compartmentalization of synaptic input - Coleman, MJ (J Neurosci, 1994)
Intra-axonal recordings of stomatogastric nerve axon 1 (SNAX1) indicate that there are synaptic inputs onto the SNAX1 terminals in the stomatogastric ganglion (STG) of the crab Cancer borealis (Nusbaum et al., 1992b). To determine whether this synaptic input only influenced SNAX1 activity within the STG, we identified the SNAX1 soma in the commissural ganglion (CoG). We found that this neuron has a neuropilar arborization in the CoG and also receives synaptic inputs in this ganglion. Based on its soma location, we have renamed this neuron modulatory commissural neuron 1 (MCN1). While intracellular stimulation of MCN1soma and MCN1SNAX has the same excitatory effects on the STG motor patterns, MCN1 receives distinct synaptic inputs in the STG and CoG. Moreover, the synaptic input that MCN1 receives within the STG compartmentalizes its activity. Specifically, the lateral gastric (LG) neuron synaptically inhibits MCN1SNAX-initiated activity within the STG (Nusbaum et al., 1992b), and while LG did not inhibit MCN1soma- initiated activity in the CoG, it did inhibit these MCN1 impulses when they arrived in the STG. As a result, during MCN1soma-elicited gastric mill rhythms, MCN1soma is continually active in the CoG but its effects are rhythmically inhibited in the STG by LG neuron impulse bursts. One functional consequence of this local control of MCN1 within the STG is that the LG neuron thereby controls the timing of the impulse bursts in other gastric mill neurons. Thus, local synaptic input can functionally compartmentalize the activity of a neuron with arbors in distinct regions of the nervous system.